Abnormal Uterine Bleeding in Premenopausal Woman - Ahmady, Wahida; Masoom, Maryam Akram (International Journal For Research In Health Sciences And Nursing, 2020)
Background and purpose: Abnormal uterine bleeding (AUB) is defined as bleeding from the uterine corpus that is abnormal in duration, volume, frequency and/or regularity. The prevalence of abnormal uterine bleeding (AUB) is estimated at 11–13% in the general population and increases with age, reaching 24% in those aged 36–40 years. The objective of this study was to describe abnormal uterine bleeding (AUB) in premenopausal women. And to determine the underlying factors and the potential for long term health consequences, decrease life quality and causes anemia and many other problems therefor valuation of the menstrual cycle should be an additional vital sign to be looked into in any female. Beginning with definition of normal menstrual cycle, evaluation, approach to diagnosis and treatment of AUB will be discussed in this paper. Outcomes evaluated include the impact of AUB on quality of life and the results of interventions including medical and surgical management of AUB.One of common treatment is the combined oral contraceptive, which is the effective treatment method to control AUB. Oral contraceptive pills (OCPs) supress endometrial development, re-establishes predictable bleeding patterns, decrease menstrual flow, and lower the risk of iron deficiency anemia.